Pengaruh Ketebalan Core Komposit Sandiwch Berpenguat Serat Pelepah Pisang-Kayu Jati untuk Aplikasi Partisi Peredam Suara pada Kamar Mesin Kapal - Indrawan, Rizal; Prasaja, Sasti (Fakultas Teknik UMSU, 2023)
Natural fiber composites are one of the innovative materials in an effort to solve the waste problem. Banana midrib and sawdust are plantation and forestry wastes whose utilization is very minimal. This research was conducted to make sandwich composites reinforced with banana midrib fiber and sawdust which is intended to be able to replace glasswool to reduce noise in the engine control room. The use of glasswool is not good for health which if the particles are inhaled it causes respiratory problems. The thickness of the core in the sandwich composite was varied by 2, 4, and 6 mm. Sound absorption testing is carried out according to the ASTM E1050-19 standard. The hand lay up method and polyester resin were used to make natural fiber sandwich composites. The highest sound absorption coefficient on specimens 2-35 is 0.77. All specimens of sandwich composites produced in this study met the requirements for sound absorption installations in buildings (ɑ = 0.15). Along with the addition of the volume fraction reinforced on the core gives a parabolic effect with the addition of 35% giving the best results at thicknesses of 2 and 6 mm. The thinner the core provides a better sound absorption coefficient than other thicknesses.